Find the sum of all integral such that the equation
has an integral solution .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Firstly, observe that the equation can be restated into: y = x 2 − 1 9 ( 5 3 ) ( 2 x − 1 ) x 2 + 1 9 ( 5 3 ) ( 2 x − 1 ) , for integers x , y . Let a = 2 x − 1 . y = x 2 − 1 9 ( 5 3 ) a x 2 + 1 9 ( 5 3 ) a = 1 + x 2 − 1 9 ( 5 3 ) a 2 ⋅ 1 9 ( 5 3 ) a Notice for y ∈ Z , ( x 2 − 1 9 ( 5 3 ) a ) ∣ ( 2 ⋅ 1 9 ( 5 3 ) a ) . From here, there are 2 cases to consider:
Case 1: When the denominator is equal to 1 or -1 Thus, x 2 − 1 9 ( 5 3 ) a = ± 1 . But substituting a = 2 x − 1 in, we get x 2 − 2 ⋅ 1 0 0 7 x + 1 0 0 7 = ± 1 . Using the quadratic formula, we see that these 2 equations have no integer solution for x . Thus, no solution for Case 1.
Case 2: When denominator = 1 , − 1
That implies that 1 9 ∣ x 2 and 5 3 ∣ x 2 . Since 1 9 and 5 3 are both primes, 1 9 ∣ x , 5 3 ∣ x .
Firstly, x can be 0 since any number divides 0 . Then, y = − 1 .
Suppose x = 0 , 1 9 ⋅ 5 3 = 1 0 0 7 ∣ x . Let x = 1 0 0 7 k , for some integer k . Then we see that the expression (of the fraction - we ignore the 1 first) becomes: ( 1 0 0 7 k ) 2 − 1 0 0 7 ( 2 ⋅ 1 0 0 7 k − 1 ) 2 ⋅ 1 0 0 7 ( 2 ⋅ 1 0 0 7 k − 1 ) = 1 0 0 7 ( 1 0 0 7 k 2 − 2 ⋅ 1 0 0 7 k + 1 ) 1 0 0 7 ( 4 ⋅ 1 0 0 7 k − 2 ) ) = 1 0 0 7 k 2 − 2 ⋅ 1 0 0 7 k + 1 4 ⋅ 1 0 0 7 k − 2 . Once again, we want the above to be an integer, hence denominator divides numerator evenly. This implies that: 1 0 0 7 k 2 − 2 ⋅ 1 0 0 7 + 1 ≤ 4 ⋅ 1 0 0 7 k − 2 1 0 0 7 k 2 − 6 ⋅ 1 0 0 7 k + 3 ≤ 0 . Using the quadratic formula, we see that the roots, k , of the equations are approximately (larger than) 0 and (smaller than) 6 . We also know that the function is an increasing one (meaning that the shape of this quadratic is a U shape - you can use differentiation or test out some small values to verify).
Hence, to find the other solutions for Case 2, you just have to try k = 1 , 2 , 3 , 4 , 5 . You will realise that k = 2 yields, x = 2 ⋅ 1 0 0 7 = 2 0 1 4 and y = 1 0 0 7 ( 2 ) 2 − 2 ⋅ 1 0 0 7 ( 2 ) + 1 4 ⋅ 1 0 0 7 ( 2 ) − 2 + 1 = 8 0 5 5 . Hence sum of all integral y is − 1 + 8 0 5 5 = 8 0 5 4 .